2013
DOI: 10.1186/1757-2215-6-78
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and oxaliplatin in sequenced combination with bortezomib in ovarian tumour models

Abstract: BackgroundOvarian cancer remains an on-going challenge mainly due to the development of drug resistance and also because the cancer is likely to have metastasized at the time of diagnosis. Currently, chemotherapy based on platinum drugs such as cisplatin is the primary treatment for the disease. Copper transporter 1 is involved in the transport of cisplatin into the cell, but is also down-regulated by the drug. Bortezomib, a proteasome inhibitor, has been reported to block this platinum-induced down-regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Al-Eisawi et al showed that bortezomib prevented the degradation of the copper transporter 1, essential for cellular uptake of platinum (40). This effect was associated with enhanced accumulation of platinum, DNA adduct formation and oxidative stress in a panel of drug-resistant ovarian cancer cell lines, lending support to our findings.…”
Section: D-ge Proteomicssupporting
confidence: 80%
“…Al-Eisawi et al showed that bortezomib prevented the degradation of the copper transporter 1, essential for cellular uptake of platinum (40). This effect was associated with enhanced accumulation of platinum, DNA adduct formation and oxidative stress in a panel of drug-resistant ovarian cancer cell lines, lending support to our findings.…”
Section: D-ge Proteomicssupporting
confidence: 80%
“…The proteasome inhibitor bortezomib is a promising novel agent in the treatment of bladder cancer; however, inducible cytoprotective mechanisms may limit its potential efficacy (15). In previous studies, bortezomib has been observed to enhance the activity of cisplatin, particularly in cisplatin-resistant cells (6,8,(16)(17)(18). The present study demonstrated for the first time that cisplatin and bortezomib combined treatment induced inhibition of cell proliferation by intrinsic and extrinsic apoptotic signaling pathways in the T24 human bladder cancer cell line.…”
Section: Discussionmentioning
confidence: 65%
“…Various studies have demonstrated that proteasome inhibition is the key regulator of intracellular protein degradation (8,9). This inhibition promotes the degradation of anti-apoptotic proteins while preventing the degradation of pro-apoptotic proteins, resulting in increased accumulation of pro-apoptotic proteins within the cells, and subsequent cell growth inhibition and programmed cell death in numerous malignant cell types (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the toxicity of bortezomib was enhanced by ER stressors and dysregulators of the UPR such as TNF in colon cancer cells (Nowis et al., 2007), the multi‐kinase inhibitor sorafenib in hepatic cancer cells (Honma and Harada, 2013), eayarestatin—an inhibitor of the ER associated ATPase p97 that retro‐translocates proteins from the ER to the proteasome—in cervical cancer cells (Brem et al., 2013), Bcl‐2 antagonists in diffuse lymphocytic B‐cell lymphoma (Dasmahapatra et al., 2009), tunicamycin and thapsigargin in pancreatic cancer cells (Nawrocki et al., 2005), and photodynamic therapy in cervical cancer cells (Szokalska et al., 2009). In ovarian cancer cells, bortezomib increased the toxicity of TRAIL (Saulle et al., 2007), histone deacetylase inhibitors (Bazzaro et al., 2008; Fang et al., 2011), carboplatin (Al‐Eisawi et al., 2013), and the natural compound indole‐3‐carbinol (Taylor‐Harding et al., 2012). Here we show that mifepristone‐induced ER stress aggravation, combined with proteasome inhibition, provides preclinical therapeutic advantage towards ovarian cancer cells—i.e.…”
Section: Discussionmentioning
confidence: 99%